The neglected governance challenges of solid waste management in Uganda: Insights from a newly created City of Mbarara - Mesharch, W. Katusiimeh; Boaz, Nabimanya; Derrick, Komwangi (African Journal of Governance and Public Leadership (AJoGPL), 2022)
e challenges of rapid urbanization threaten governance of many urban centers especially in developing countries. However, to achieve these challenges, the gaps in governance of waste management need to be addressed. ere is no comprehensive analysis examining the governance related challenges in solid waste management (SWM) even when a large body of research indicates that governance issues are highly signi cant in the eff ective delivery services. is paper addresses this question: What solid waste management governance challenges must be addressed to avoid the problems of the past? is study was carried out in the City of Mbarara. A semi-structured in-depth interview was chosen as the method for qualitative data collection. In-depth interviews were administered to city solid waste managers, managers of private sector companies in SWM, political leaders especially local councilors and opinion leaders. ese respondents were purposely sampled. Findings reveal that the organization of solid waste management is poor exempli ed by weak capacity, poor implementation of laws and regulations, poor record management, misappropriation of funds among others. ere is therefore need to strengthen capacity ( nancial, institutional, technological and infrastructural) to drive environmentally solid waste management practices for sustainable solid waste management.